Eligibility for growth hormone therapy in children born small for gestational age is substantially lower than expected. (3rd May 2021) - Lavi, Eran; Shafrir, Asher; Halloun, Rana; Basel, Itai; Eventov Friedman, Smadar; Abu‐Libdeh, Abdulsalam; Shoob, Hanna; Stein‐Zamir, Chen; Zangen, David Haim
Abstract: Background: Growth hormone therapy is indicated for children who are both born 'small for gestational age' (SGA) and do not achieve adequate catch‐up growth (ACUG). Objective: To evaluate the actual incidence of infants born SGA and their actual ACUG. Methods: Birth weight data from the newborn registry at two hospitals were analysed during four consecutive years. SGA was defined according to WHO parameters and the corresponding Israeli criteria. Follow‐up measurements of height and weight were abstracted from either the Ministry of Health—child growth follow‐up centres, or their paediatrician clinic. ACUG was declared when the height reached was above −2.5 or −2 standard deviations (SDS) from the mean for age and gender. Results: Out of 43 307, only 524 babies in the cohort (1.2%) were SGA (52% of expected). This finding was consistent annually. Out of the 446 SGA born children with available growth data (85%) during 4‐8 years, 405 children (90.8%) reached a height greater than −2SDS and 428 (96%!) reached a height greater than –2.5 SDS. Term children had higher rate of ACUG achievement as compared to preterm 97.2% vs 86.8% ( P < .001). Birth week and birth weight were also related to achievement of ACUG ( P < .001). Conclusion: This large representative, heterogeneous and Western Caucasian cohort indicates that the actual number of SGA newborns is nearly half of the expected and that the actual prevalence of ACUG is also significantly higher than previously reported. These findings may have an impact on morbidity, health cost planning and growth hormone requirements in SGA babies.